Empowerment of women (New Delhi : Anmol, 1998)
Papers presented at the National Convention 1995 on Empowerment of Women: Nairobi ('85) to Beijing ('95) held in Dhaka, Bangladesh, during March 16-18, 1995.
Includes bibliographical references.
Keywords: Women -- Political activity -- Bangladesh -- Congresses; Women in development -- Bangladesh -- Congresses; Women -- Government policy -- Bangladesh -- Congresses